Seasonal variation in waterbird assemblage in the Mahango Game Reserve, north-eastern Namibia - Kopij, Grzegorz; Paxton, Mark (Water SA, 2019)
There are few African studies on seasonal changes in the waterbird assemblages in river ecosystems. Tropical freshwater ecosystems are regarded as more stable habitats over the year than terrestrial ones. The same could be expected in regard to the bird fauna associated with such ecosystems. In order to test if waterbird asembalges followed the stable ecosystem paradigm a study was undertaken in the Okavango River, in the Mahango Game Reserve, north-eastern Namibia. Counts of all waterbirds were conducted in wet and dry seasons during 2001–2006. In total, 88 waterbird species were recorded. In wet seasons the number was slightly lower (N = 75) than in dry seasons (N = 78) (chi-square test: χ2 = 0.06; p > 0.05). The total number of individuals of all resident species recorded in wet seasons was unexpectedly much lower in wet (N = 9 979) than in dry seasons (N = 15 501) (chi-square test: χ2 = 1 196; p < 0.01). In wet seasons, Collared Pratincole, Blacksmith Lapwing, African Openbill Stork and African Darter dominated (58.8%), while in the dry season: White-faced Duck, Spur-winged Goose, African Skimmer, African Reed Cormorant, African Darter and Squacco Heron contributed 60.8% to the overall abundance. Diversity indices were similar in both seasons.